2019
DOI: 10.3390/jcm9010091
|View full text |Cite
|
Sign up to set email alerts
|

Why Uptake of Blended Internet-Based Interventions for Depression Is Challenging: A Qualitative Study on Therapists’ Perspectives

Abstract: 1) Background: Blended cognitive behavioral therapy (bCBT; online and face-to-face sessions) seems a promising alternative alongside regular face-to-face CBT depression treatment in specialized mental health care organizations. Therapists are key in the uptake of bCBT. This study focuses on therapists' perspectives on usability, satisfaction, and factors that promote or hinder the use of bCBT in routine practice; (2) Methods: Three focus groups (n = 8, n = 7, n = 6) and semi-structured in-depth interviews (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
51
0
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 35 publications
15
51
0
17
Order By: Relevance
“…The interviewed GPs reported not to be familiar with bPT, to have little knowledge of it, and to prefer more information and training. This is in accordance with the results of studies on bPT in GPs [ 58 ] and psychotherapists [ 56 ] and stand-alone IMIs in GPs [ 42 , 60 ] and health professionals [ 61 ]. GPs also asked for more feedback and professional exchange regarding the treatment, consistent with requests by professionals in previous research on IMIs [ 57 ] and with GPs’ reported facilitators for referrals to IMIs [ 41 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The interviewed GPs reported not to be familiar with bPT, to have little knowledge of it, and to prefer more information and training. This is in accordance with the results of studies on bPT in GPs [ 58 ] and psychotherapists [ 56 ] and stand-alone IMIs in GPs [ 42 , 60 ] and health professionals [ 61 ]. GPs also asked for more feedback and professional exchange regarding the treatment, consistent with requests by professionals in previous research on IMIs [ 57 ] and with GPs’ reported facilitators for referrals to IMIs [ 41 ].…”
Section: Discussionsupporting
confidence: 90%
“…The most frequently named barriers by the interviewed GPs concerned the use of new technologies within blended treatments, as most assumed that some patients would not be familiar with internet and technology or would be skeptical and uncertain as to whether an internet-based intervention could help them. These findings are in line with earlier research on barriers to the use of bPT by psychotherapists [ 34 , 35 , 55 , 56 ] as well as IMIs by clinicians (psychiatrists or GPs or psychologists) [ 57 ] or by GPs [ 42 ]. Furthermore, GPs’ concerns regarding data safety were also mentioned in previous research on bPT by GPs [ 58 ] and psychotherapists [ 34 , 35 , 55 ] as well as on IMIs by GPs [ 42 ] and psychotherapists [ 59 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Of particular interest is the concept of organisational implementation climate which can be de ned as the shared meaning (or disagreement) staff members attach to organisational events, practices and procedures they experience and the behaviours they see being rewarded, supported, and expected in implementing evidencebased practices [23][24][25][26]. Organisational implementation climates are possibly relevant to investigate as they are known to shape staff members' attitudes towards adopting and implementing evidence-based interventions into daily practice [24,25,27] and professionals perceptions are of particular interest in successfully implementing new interventions [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the challenges, the authors are highly optimistic about the potential of DMHS to reduce the global burden of the high prevalence of mental health disorders. Elaborating on dissemination of Internet-delivered treatment in routine care, the paper of Mol et al [ 4 ] describes a qualitative study targeting therapists’ perspectives of blended Internet-delivered interventions, specifically, cognitive behavioural therapy (CBT). In blended Internet-delivered interventions, face-to-face treatment with a therapist was combined with online therapy.…”
mentioning
confidence: 99%